2023
DOI: 10.1111/den.14573
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an artificial intelligence‐aided endoscopic diagnosis system on improving endoscopy quality for trainees in colonoscopy: Prospective, randomized, multicenter study

Abstract: ObjectiveThis study was performed to evaluate whether the use of CAD EYE (Fujifilm, Tokyo, Japan) for colonoscopy improves colonoscopy quality in gastroenterology trainees.MethodsThe patients in this multicenter randomized controlled trial were divided into Group A (observation using CAD EYE) and Group B (standard observation). Six trainees performed colonoscopies using a back‐to‐back method in pairs with gastroenterology experts. The primary end‐point was the trainees' adenoma detection rate (ADR), and the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…Polyp detection (CADe) for the CAD EYE system has been evaluated in a recent study by Neumann et al, which showed that it achieved 100% sensitivity in polyp detection and a negligible false-positive frame rate 14 . Its impact on the quality of endoscopies of trainee gastroenterologists has been highlighted in a study by Yamaguchi et al, where the adenoma miss rate was decreased in the CAD EYE group; however, the authors noted no improvement in adenoma or polyp detection rate 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Polyp detection (CADe) for the CAD EYE system has been evaluated in a recent study by Neumann et al, which showed that it achieved 100% sensitivity in polyp detection and a negligible false-positive frame rate 14 . Its impact on the quality of endoscopies of trainee gastroenterologists has been highlighted in a study by Yamaguchi et al, where the adenoma miss rate was decreased in the CAD EYE group; however, the authors noted no improvement in adenoma or polyp detection rate 22 .…”
Section: Resultsmentioning
confidence: 99%
“…However, after about 200 experiences of cases, these rates for the last 50 lesions increased 88.0%/95.2% for non-experts. Another study examined the efficacy of CAD EYE for lesion detection by 6 trainees with experience of ≤20 colonoscopies[ 22 ]. The ADR between observation with CAD EYE group and standard observation group were not significant (58.4% vs. 61.0%, p=0.690).…”
Section: Discussionmentioning
confidence: 99%
“…However, eight of these 15 trials reported a significant improvement for a secondary endpoint. [21][22][23][24][25][26][27][28]…”
Section: What Models Are Being Deployed?mentioning
confidence: 99%